(INTER)PERSONAL STATEMENTS: A DISCURSIVE ANALYSIS OF COLLEGE APPLICATION ESSAYS WRITTEN IN ENGLISH BY US AMERICAN AND BRAZILIAN STUDENTS - do Monte Junior, José Orlando Cardoso (Revista X, 2019)
The field of discourse analysis has produced extensive research on various aspects of genres that permeate everyday life as well as on the specialized discourses of academic and professional communities. Nevertheless, there is a dearth of studies on the personal statement, which, despite being a key genre of the admissions processes to globalized (and English language-dominated) institutions of higher education, remains unexplored in Brazilian educational culture. The present study addresses this gap by examining samples of this unique genre produced by US American and Brazilian students admitted to English-language universities. The analysis principally draws from Dominique Maingueneau’s scholarship on the “scene” of a genre and the Bakhtin Circle’s ideas on the social and generic nature of utterances. The main purpose is to compare and contrast rhetorical appeals to ethos and pathos made by both groups of students engaged in the high-stakes enterprise of writing about their values, beliefs, and goals with unknown readers/evaluators in mind. The results shed light on some of the linguistic and intercultural challenges that Brazilian students face when communicating in English within unfamiliar scenes of writing, the knowledge of which can shed light on ways to facilitate successful intercultural communication.